Unlocking Teacherpreneur Potential in Higher Education: Validating a Competency Measurement Scale - Dihui Liu; Sukanya Chaemchoy; Pruet Siribanpitak (MDPI AG, 2024)
This study investigated the level of teacherpreneur competency among pre-service teachers (n = 400), with an additional 400 pilot participants from the same academic context invited for exploratory factor analysis and reliability analysis. A self-reported questionnaire, adapted from the Teacherpreneur Competency Model (TCM), was used to assess participants' competency across four key domains: pedagogical, social, personality, and professional. The findings revealed that pre- service teachers possessed high levels of teacherpreneur competency, with Personality Competency scoring the highest and Social Competency scoring the lowest. These results suggest that while pre-service teachers have a solid foundation in delivering instruction, targeted interventions are needed within teacher education programs to nurture their entrepreneurial spirit and foster the social and personal attributes associated with teacherpreneurship. This study underscores the importance of integrating comprehensive competency development into teacher education curricula to better prepare future educators for the dynamic demands of the teaching profession.